2017
DOI: 10.3390/rs9070667
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Pauscher, L., et al. An Inter-Comparison Study of Multi- and DBS Lidar Measurements in Complex Terrain. Remote Sens. 2016, 8, 782

Abstract: The authors would like to correct the following errors in [1]. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(2 reference statements)
0
1
0
Order By: Relevance
“…Along the lines of obtaining the best possible data from wind lidar, a methodology for field calibration of nacelle-based lidar was presented by Borraccino et al [11] and a comparison of lidar data observed using three scanning lidars directed to one point versus a profiling lidar installed in complex terrain was presented by Pauscher et al [12,13]. The latter result is important for site assessment in complex terrain.…”
Section: Introductionmentioning
confidence: 99%
“…Along the lines of obtaining the best possible data from wind lidar, a methodology for field calibration of nacelle-based lidar was presented by Borraccino et al [11] and a comparison of lidar data observed using three scanning lidars directed to one point versus a profiling lidar installed in complex terrain was presented by Pauscher et al [12,13]. The latter result is important for site assessment in complex terrain.…”
Section: Introductionmentioning
confidence: 99%